La Gazeta de Valencia de 1812 - Gérard Dufour (El Argonauta Español)
The collection of the Gazeta de Valencia, published in 1812 under the control of Mariscal Suchet, stored in the Biblioteca Valenciana, provides important information on the relationship between Suchet and the King Joseph I. In addition to the traditional informationconcerning the condition of the subscription, the prologue, published on the 1st of February, 1812 (one month after the arrival of Frencharmy in Valencia), shows clearly that the Marshal of the Empire acted on behalf of Napoleon and paid less attention to his brother. The independence of Suchet with regard to Joseph also becomes apparent in the choice of news from Madrid, which were carefully chosen with the aim of not overshadowing Duke of Albufera. By the time when the « rey errante » retired in Valencia, the Gazeta de Valencia continued in the hands of Suchet, despite the fact that Llorente, one of the accredited propangandists of the new dynasty along with Moratin and Estala, collaborated in the Gazeta, Not being able to spread the journal in the former Kingdom of Valencia (Alicante was never occupied by the imperial army), Suchet managed to spread the correspondence of auxiliary bishop Miguel Suarez de Santander, which was published in the Gazeta in Zaragoza. Therefore, the Gazeta stand for the official organ of journal in the viceroyalty, that Aragon and Valencia represented for Suchet.